Réponses

2013-04-29T20:04:18+02:00

40)

 a)

 

3x+2=2x-5

3x-2x=-5-2

x=-7

 

b)

 

-3x+7=3x-11

-3x-3x=-11-7

-6x=-18

x=-18/-6

x=3

 

41)

 

a)

 

-5x+4=6x+8

-5x-6x=8-4

-11x=4

x=4/-11

 

b)

 

5-9x=-3x+2

-9x+3x=2-5

-6x=-3

x=-3/-6

x=0.5

 

42)

 

a)

 

2(x-5)=3x+5

2*x+2*5=3x+5

2x+10=3x+5

2x-3x=5-10

-x=-5

x=5

 

b)

 

-4(3+x)=2x-6

-4*3-4*x=2x-6

-12-4x=2x-6

-4x-2x=-6+12

-6x=6

x=6/-6

x=-1

 

43)

a)

 

-3(2+x)=1-5x

-3*2-3*x=1-5x

-6-3x=1-5x

-3x+5x=1+6

2x=7

x=7/2

x=3.5

 

b)

 

4-7(2-x)=5-4x

4-7*2-7*(-x)=5-4x

4-14+7x=5-4x

7x+4x=5-4+14

11x=15

x=15/11

 

 

2013-04-29T20:04:59+02:00

40) 3x+2 = 2x-5                  -3x+7=3x-11

       x +7 = 0                         -6x+18=0

       x=-7                                x=3

 

41) -5x +4= 6x+8             5-9x=-3x+2

      -11x-4=0                      3-6x=0

       x= 4/-11                       x= 1/2

 

42)2(x-5)=3x+5              -4(3+x)=2x-6

     2x-10=3x+5               -12-4x=2x-6

     -x-15=0                         -6x-6=0

    x= -15                             x= -1

 

43) -3(2+x)=1-5x          4-7(2-x)= 5-4x   

      -6-3x=1-5x                4-14+7x= 5-4x

     -7+2x=0                     -10+7x=5-4x

     x= 7/2                            -15+11x=0

                                          x= 15/11